The Moderating Role Of Economic Growth In The Association Between Corruption And Poverty In Indonesia - Al Hazmi, Raldin Alif (Journal of Law, Administration, and Social Science, 2024)
Indonesia has abundant natural and human resources. With a large population and abundant natural resources, Indonesia has the potential to become the centre of the world economy. But in reality, Indonesia faces many challenges. With such abundant wealth, corruption, economic growth, and poverty are the biggest problems in Indonesia. Corruption is closely related to the economic condition of society. This study aims to analyse the impact of corruption on the poverty rate in Indonesia. Using secondary data published by the Central Bureau of Statistics (BPS) from 2018 to 2022, a panel data regression model in 34 provinces in Indonesia was used to obtain 170 data samples. The researcher found that the Corruption Perception Index (CPI), which is considered an indicator of the level of corruption in Indonesia, has a negative and significant impact on the poverty rate. On the other hand, GR as an indicator of economic growth in Indonesia has a negative and significant impact on Indonesia's economic growth. In this study, economic growth is able to moderate the interaction relationship between corruption and poverty levels in Indonesia. Although Indonesia in the 2018-2022 timeframe has always experienced growth, this is also in line with the higher level of corruption in Indonesia, which has an impact on the high disparity and poverty in Indonesia. Therefore, the government and society must work together to fight corruption and reduce poverty by improving transparency and increasing public participation in order to reduce inequality and poverty among Indonesians.